Ruptured popliteal artery aneurysm: case report (Brazilian Journal of Health Research, 2024)
Introduction: Popliteal artery aneurysm is the most common peripheral arterial aneurysm, although rare in the general population, and carries a high risk of severe complications, especially when rupture occurs. Objectives: To report the case of a patient with a ruptured popliteal artery aneurysm, describing the clinical presentation, diagnostic imaging findings, and therapeutic management. Methods: Case report of an 83-year-old male patient with multiple comorbidities, admitted with intense pain and a pulsatile mass in the right popliteal fossa; clinical examination, Doppler ultrasonography, CT angiography, and arteriography were performed for diagnostic confirmation, followed by open surgical repair with revascularization. Results: Imaging revealed a 9-cm popliteal aneurysm with contained rupture extending to the tibioperoneal trunk; the patient underwent a superficial femoral–posterior tibial bypass using reversed ipsilateral great saphenous vein, hematoma evacuation, and drainage. He showed satisfactory postoperative vascular recovery and graft patency, later developing limb lymphedema and surgical-site infection requiring readmission and clinical management, with good final evolution. Conclusion: A ruptured popliteal artery aneurysm is a vascular emergency with high risk of limb loss and death, requiring early diagnosis and immediate surgical intervention; open repair with revascularization proved effective, highlighting the importance of prompt management and postoperative follow-up to prevent further complications.
Keywords: Popliteal artery aneurysm; Ruptured popliteal aneurysm; Surgical treatment